As leis do sistema prisional do Brasil: o trabalho como pena e a educação como direito - Cunha, Poliane Lira (Brasil, 2025)
This Course Completion Work is methodologically structured in a bibliographical and documentary research that addresses the theme of education linked to the theme of work in the prison system, based on the following research problem: How did the historical process of insertion of work and education into the system occur? Brazilian prison? To respond to the problem, we established the general objective of understanding how and under what contexts work as an obligation and the right to education were historically introduced and how they appear described in the legislation that regulates the penalty of restriction and deprivation of liberty. The analysis is structured around the following specific objectives: to understand, through bibliographic and documentary research, the historical path of the organization of the Brazilian legal system and the constructions of our criminal legislation; investigate the terms that are related to work and education in the legislation that guides the country's penal system; systematize legal assistance and support equipment for inmates at national and state levels and understand the relationship with work and education in these systems. Finally, the study concluded that work, as a punishment, was widely addressed in the first regulations, both in the Portuguese Ordinances and in the Criminal Codes of 1830 and 1890, however, when it became a right, there was a lack of approach to the topic in the current legislation and that education only began to be offered as a right after the Penal Execution Law of 1984 with a professional and systematic nature.